Burning controversies in NETs and autoimmunity: The mysteries of cell death and autoimmune disease - Nishant Dwivedi; Marko Radic (Taylor & Francis Group, 2018)
The causes and mechanisms of autoimmune disease pose continuing challenges to the scientific community. Recent clues implicate a peculiar feature of neutrophils, their ability to release nuclear chromatin in the form of neutrophil extracellular traps (NETs), in the induction or progression of autoimmune disease. Efforts to define the beneficial versus detrimental effects of NET release have, as yet, only partially revealed mechanisms that guide this process. Evidence suggests that the process of NET release is highly regulated, but the details of regulation remain controversial and obscure. Without a better understanding of the factors that initiate and control NET formation, the judicious modification of neutrophil behaviour for medically useful purposes appears remote. We highlight gaps and inconsistencies in published work, which make NETs and their role in health and disease a puzzle that deserves more focused attention.